Pelatihan bahasa Inggris Dasar Bagi Remaja Masjid Musholla Al-Ikhlas Hawila Kelurahan Namo Bintang Kec. Pancur Batu - Kandri S.Pd, MS (Cattleya Darmaya Fortuna, 2024)
This community service (PKM) is focused on basic English language training for Al-Ikhlas Hawila Mosque Youth, Namo Bintang village, Pancur Batu sub-district. The background to this training was the low English language skills of the youth or teenagers at the Hawila mosque (Musholla). he objectives to be achieved in this PKM include: 1) helping to improve the English language skills of mosque youth or teenagers through conversation training activities, 2) providing an understanding of how to make basic English sentences, 3) providing opportunities and work experience for lecturers and students, 4) fostering cooperation with various related parties, especially the prayer room, as a collaboration to introduce the Akademi Pariwisata Nusantara Medan to the community. The method used to achieve this PKM goal is through lectures and training. Training-related materials are delivered through lectures and discussions. Then the training is carried out directly with direct practice.